A numerical analysis on double acting pneumatic telescopic cylinder motion characteristics - Din, Abdul Talib (IACSIT, 2010)
This paper presents the design and development of a mathematical model of dynamic motion of pneumatic telescopic cylinder. The aim of the research is to develop a telescopic pneumatic system that can handle variable load at constant forward and retracting speed. The design analysis carried out is focused and based mainly on identifying the characteristics of the pneumatic cylinder using force-feedback control system. A conceptual model was made and the limitations were identified and further studied on nonlinear behavior and the solutions to improve its characteristics were sought in the process of designing and developing the telescopic cylinder. The control system contained combination of proportional and on-off valve in controlling the telescopic cylinder movement. The determination of the displacement of each stage of the telescopic cylinder, velocity and acceleration were optimized using multi-order PI controller. Method of research is performed by simulation studies using Matlab Simulink to prove the dynamic mathematical modeling of the cylinder. During the last stage of the research, a scale down model of the telescopic cylinder was fabricated incorporating all design aspects derived from the theoretical and simulation analysis. After that an experimental study was conducted on the scale down cylinder in order to validate the data obtained. The validated data shall be used in the design of the full scale of the telescopic cylinder. It is found that from the numerical analysis, the designed system can achieve a constant speed although loaded with varied axial force.